Beyond the Price Tag: How Quality Transformation Drives Parental Trust and School Choice in Islamic Education - Qomusuddin, Ivan Fanani; Fatimah, Nur; Sapitri, Wina; Latifah, Siti; Arifin, Bambang Samsul; Wemama, A-eshah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of education costs and school quality on school choice decisions and to examine the mediating role of school quality in this relationship in the context of Islamic primary education. This study used a quantitative approach, administering a Likert-scale questionnaire to 168 parents of students. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach in SmartPLS to test direct and indirect relationships among variables. The results showed that education costs had a positive and significant effect on school choice decisions (β = 0.187; p < 0.05) and on school quality (β = 0.554; p < 0.001). In addition, school quality had a strong effect on school choice decisions (β = 0.663; p < 0.001) and significantly mediated the relationship between education costs and school choice decisions (β = 0.368; p < 0.001). This research provides implications that strategies to improve school quality should be prioritized in Islamic basic education policies, accompanied by transparency in the management of education costs, to increase parental trust and strengthen the competitiveness of educational institutions in a sustainable manner.